Body Weight Comparison Before and After Pregnancy in Patients Treated at an Ecuadorian Hospital - Patricio Jaramillo Guerrero; María de Lourdes Llerena Cepeda; Manuel Conrado Ezcurdia Bárzaga (Medisur)
Foundation: nutrition is vital during the reproductive period and is a potentially modifiable risk factor. The nutritional status of future mothers is a good predictor of perinatal and long-term outcomes for the baby and the mother. Low-weight pregnant women are also exposed to a greater risk of premature birth and having small-for-gestational-age neonates. Objective: to compare body weight before and after pregnancy in patients treated at an Ecuadorian hospital. Method: a descriptive and retrospective study was carried out on pregnant women treated at the Ecuador coastal region hospital during 2022. The sample was obtained by simple random sampling and consisted of 287 patients. The SPSS 27.0 program was used to analyze the data, to determine the significance levels the Student's t test was performed. Results: a predominance of pregnant women between 30 and 39 years of age was found. The mean weight of the patients before and after pregnancy was 61.02 and 63.14 kg respectively, for a statistically significant difference. Conclusions: the findings indicated a notable increase in the body weight of the pregnant patients under research. This study provided significant data about variations in body weight during the pregnancy period in the Ecuador specific context, which could have important implications for the medical care and health management of future mothers.